Polarization of Low-Grade Inflammatory Monocytes Through TRAM-Mediated Up-Regulation of Keap1 by Super-Low Dose Endotoxin - Rahtes, Allison; Li, Liwu (Frontiers in Immunology, 2020)
Abstract: Subclinical endotoxemia (low levels of bacterial endotoxin (LPS) in the blood stream) has been correlated with chronic inflammatory diseases, with less-understood mechanisms. We have previously shown that chronic exposure to super low doses of LPS polarizes monocytes/macrophages to a pro-inflammatory state characterized by up-regulation of pro-inflammatory regulators such as p62 and simultaneous down-regulation of anti-inflammatory/resolving regulators such as Nrf2. Building upon this observation, here we show that chronic exposure to super-low doses of LPS leads to accumulation of the Nrf2-inhibitory protein Keap1 in murine monocytes. This is accompanied by increases of p62 and MLKL, suggesting a disruption in autophagy completion by super-low dose LPS. Consequently, monocytes subjected to persistent super-low dose LPS challenge accumulate higher levels of IKKβ and NFkB, and polarized to an inflammatory state represented by higher expression of inflammatory marker Ly6C as well as lower expression anti-inflammatory marker CD200R. Further analysis revealed that Keap1 levels are significantly enriched in the Ly6Chi pro-inflammatory monocytes. Finally, we show that the TLR4 signaling adaptor TRAM is essential for these effects. Together our study provides novel insight into signaling mechanisms behind low-grade inflammatory monocyte polarization unique to chronic super-low dose LPS exposure.